A Study of Merge-Conflict Resolutions in Open-Source Software. - Eriksson, Isak; Wållgren, Patrik (My University, 2016)
In collaborative software development, conflicts often arise when merging different versions of the code. These are often solved manually, which slows down productivity. To develop a tool that assists in the resolution process, we aim to study how developers resolve conflicts and try to categorize the resolutions. We do this by studying large open-source projects on GitHub. We found that for conflicts regarding code inside methods or constructors, the currently checked out version was chosen in 77% of the cases. We found that developers tend to choose their own version of the code when resolving merge-conflicts.
Keywords: Data- och informationsvetenskap; Computer and Information Science